Pemodelan Sistem Pakar Untuk Menentukan Penyakit Diabetes Mellitus Menggunakan Metode Naive Bayes Studi Kasus : Puskesmas Poncokusumo Malang - Irwan Andriyanto; Edy Santoso; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Preventation of diabetes mellitus bale to do if the patient knows the signs of diabetes mellitus. But people has difficulties to find it's signs. Because the expert in this subject is very less and the cost so expensive. That's why people need to help to prevent this deases by knowing it's signs by using expert system. One of method can use to know diabetes mellitus is Naive Bayes. Naive Bayes a statistic approach to do induction inferency in classification matter. This methode use probability. The basic of Naive Bayes is Training Data. Training Data is Diabetes Mellitus and it's signs that get from research object. The result comes from the biggest probability. Functional test gets 100%. It's means that the system works well. Bigger training data will get higher system accuration. The best accuration is 100% comes from 140 data training.